The Utilization of CCTV at Certain Points by Cimahi Traffic Police Department in Minimizing Congestion - Puspa Anggitha Sanjaya (Advances in Police Science Research Journal, 2021)
The Legal Area for Cimahi Police is one of the Polres with a high level of congestion, because the area is a mountainous area and is a crossing area to the capital city of Bandung. This area is a tourist area and part of it is an industrial area. The Cimahi Police with the idea of ​​placing CCTV at certain points by the Cimahi Police traffic unit which is a prone point for congestion, accidents and traffic violations in the hope of monitoring the traffic flow in the Cimahi Police jurisdiction. The purpose of this research is to find out how the use of CCTV at a certain point by the Cimahi Police Precinct to minimize congestion, Determine the location of CCTV installation, How to act Cimahi Police Traffic in utilizing CCTV to minimize congestion, and the operator control patterns and CCTV use. The theory used in this research is POAC management theory, attitude and behavior theory, technology acceptance model, traffic engineering management theory. With the concept of CCTV technology, certain points, minimize traffic jams. This type of research is qualitative with data collection techniques by observation, documentation, and interviews. The results of this study indicate that the use of CCTV by the Traffic Police of Cimahi Police has not been able to minimize existing congestion, because not all vulnerable points have been installed with CCTV, there is no public awareness of orderly driving, narrow roads for large vehicle volumes. So it is necessary to have socialization for the public regarding CCTV monitoring and the importance of orderly traffic.